Evaluating Midwives Communication Skills from the Perspective of Parturient Women Attending to Hospitals for Delivery - Maryam Sadat Katebi; Talat Khadivzadeh; Zohre Sepehri Shamloo; Habibolah Esmaily (Mashhad University of Medical Sciences, 2017)
Background & aim: Communication is a fundamental human need. Medical students and healthcare professionals must be attuned to the needs of patients using effective communication skills. With regards to medical training, currently the focus is on theoretical matters and communication skills are taken for granted. This problem has caused miscommunication with patients referred to teaching hospitals. We conducted this study to assess communication skills of midwives from the perspective of parturient women. Methods: In this descriptive study, we evaluated 50 midwives working in maternity wards of Ghaem, Imam Reza, Omolbanin, and Hasheminejad hospitals in Mashhad, Iran. Three parturient women were selected per one midwife in a maternity ward. The parturient women participating in this study were in labor, delivery, admission or postpartum stages and completed the Interpersonal Communication Skills inventory by interview. To analyze the data, descriptive statistics, t-test, ANOVA, and Pearson product-moment correlation were performed, using SPSS 16. Results: The mean scores of communication behaviors of midwives with parturient in delivery, admission, and postpartum stages were 92.61±10.81, 93.31±10.59, and 94.19±8.26, respectively. Between the previous delivery of parturient, with communication behavior of midwives in the stage of admission or post-partum (P=0.015) and satisfaction of pregnancy with communication behavior of midwife in labor stage (P